Creolization and the Production and Negotiation of Boundaries in Breyten Breytenbach's Recent Work - Viljoen, Hein (Nordlit, 2009)
Much of the South African poet Breyten Breytenbach's work has been concerned with borders. In this article I examine borders and creolization in three important poems from Nine landscapes of our time bequeathed to a beloved (Nege landskappe bemaak aan 'n beminde, 1993), Paper flower (Papierblom, 2002) and The wind-catcher (Die windvanger, 2007). The link between creolization and boundaries is the poet's conception of identity and freedom. As is often the case the boundaries of the self are questioned as the poet permutates the central concepts. Crossing boundaries entails entering into dialogue not only with the self but also with the mother tongue itself and with a variety of other artists and writers. In other words, in Breytenbach's work an abrogation and appropriation of the own tradition ("erfgoed") as well as of material from others, other places and other traditions occur. In these three case studies in particular it is clear how the poet stretches and deforms boundaries as part of his poetic project to concretize a dynamic freedom.
Keywords: Nine landscapes of our time bequeathed to a beloved (Nege landskappe bemaak aan 'n beminde; 1993); Paper flower (Papierblom; 2002); The wind-catcher (Die windvanger; 2007); creolization; boundaries; freedom; abrogation; appropriation